The Cleveland Clinic Manual of Headache Therapy Second Edition - Tepper, Stewart J.; Tepper, Deborah E. (Springer International Publishing : Imprint: Springer, 2014)
Since The Cleveland Clinic Manual of Headache Therapy published, new guidelines and therapies have emerged.  The Cleveland Clinic Manual of Headache Therapy, 2nd Edition provides these advances, as well as a number of clinical challenges not covered in the 1st edition - including headaches associated with opioids and traumatic brain injury.  Organized by dedicated parts and chapters on diagnosis and treatment, this practical guide also features clinical pearls and summarizing tables.  The Cleveland Clinic Manual of Headache Therapy, 2nd Edition will provide neurologists, pain specialists, fellows, residents and primary care physicians an evidence-based resource of clinical approaches and appropriate treatments.